2015
DOI: 10.4137/sart.s20148
|View full text |Cite
|
Sign up to set email alerts
|

Gasoline Abuse in a 10-Year-Old Child with Mental Retardation: A Case Report

Abstract: Inahalant abuse is of increasing interest in India. The age of onset is typically during adolescence. Gasoline inhalant use is rarely reported in adolescents with intellectual deficit. We report a case of petrol dependence in a 10-year-old child with mental retardation. Possible effect of petrol huffing on behavior and cognition is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Another case reported that a 13-year-old girl was addicted to fumes of petrol, later she started sniffing cloth soaked in petrol and kerosene for one year and signs of becoming violent, pleasant feeling, loss of appetite concluded that she was experiencing inhalant abuse and was later confirmed by interviewing by Pahwa 29 . Another case by Joshi and Vankar was about a 10-year-old boy huffing and sniffing petrol from vehicles, his parents observed over activeness, hangover like behavior, dizziness, restlessness and inattention 30 . In other study, reported by Gautam a 22-year-old boy with a history of sniffing kerosene, petrol and diesel for past eight years on daily basis and on examination revealed poor grooming, delayed speech, insomnia and increased psychotic activity.…”
Section: Gasolinementioning
confidence: 99%
“…Another case reported that a 13-year-old girl was addicted to fumes of petrol, later she started sniffing cloth soaked in petrol and kerosene for one year and signs of becoming violent, pleasant feeling, loss of appetite concluded that she was experiencing inhalant abuse and was later confirmed by interviewing by Pahwa 29 . Another case by Joshi and Vankar was about a 10-year-old boy huffing and sniffing petrol from vehicles, his parents observed over activeness, hangover like behavior, dizziness, restlessness and inattention 30 . In other study, reported by Gautam a 22-year-old boy with a history of sniffing kerosene, petrol and diesel for past eight years on daily basis and on examination revealed poor grooming, delayed speech, insomnia and increased psychotic activity.…”
Section: Gasolinementioning
confidence: 99%